Effect of Tourism Experience Dimensions on Tourism Satisfaction and Tourism Loyalty - Anisatul Fauziah; Jesi Irwanto (Jurnal Ilmu Manajemen Advantage, 2020)
A strong Tourism Experience dimension gives tourism satisfaction which in the end creates tourists loyalty. The Tourism Experience can be reflected in sense, feel and think on tourist attraction felt by tourists. The objective of this research is to test the effect of Tourism Experience dimensions consists of significant sense, feel and think partially and simultaneously on tourism satisfaction and tourists loyalty. Test the effect of satisfaction on loyalty and test the satisfaction as a mediator of sense, feel and think on tourists loyalty. The respondents in this study were 200 B29 tourists. The path analysis and single-test testing showed that sense, feel and think had a significant effect simultaneously on satisfaction and loyalty. Partially, only sense and satisfaction had a significant effect on loyalty, meanwhile feel and think had no significant effect on tourists loyalty partially. The satisfaction is proven to mediate the effect of think on loyalty, but it is not proven to mediate the effect of sense and feel on tourists loyalty.